Sediment Metal Contamination, Bioavailability, and Oxidative Stress Response in Mangrove Avicennia marina in Central Red Sea - Alhassan, Abdullahi Bala; Aljahdali, Mohammed Othman (Frontiers in Environmental Science, 2021)
Anthropogenic activities have been on the increase in the urban environment and have led to contamination of the environment with toxic metals. However, mangrove plants' response to heavy metal stress due to anthropogenic activities explains the metal bioavailability and its potential ecotoxicological effect. We carried out a multi-approach study to investigate i) if metals (Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Mo, Cd, Pb, Sr and V) concentrations in mangroves at the central Red Sea are due to the anthropogenic influence and are above the sediment quality guidelines ii) if an increase in metal concentration influence height and antioxidant enzyme (Catalase; CAT, Glutathione S- transferase; GST and Superoxide dismutase; SOD) activities in A. marina. There were significant variations (P < 0.05) in metal concentrations and antioxidants across the six mangrove stands with higher concentrations at Al lith (LT) and South Jeddah (SJ). Even though the concentrations of metals in mangrove leaves are slightly higher in LT than SJ, principal component analyses showed that higher concentrations of Cr, Co, Zn, Cd and Pb in mangrove leaves from SJ, influence higher antioxidant enzymes activities and the lowest average mangrove height (2.01 m). This suggests that the higher metal concentrations be factors for the biggest stress in these mangrove ecosystems. However, among the 13 metals, Cr (82.07 mg/kg), Cu (41.29 mg/kg) and As (10.30 mg/kg) in sediment have values within the ERL range of probable effect, while Ni (53.09 mg/kg) was above ERM threshold. Hence the need to focus on monitoring these metals in mangrove sediments and their anthropogenic sources.